A case of multicentric gliomas in both supra- and infratentorial regions with different histology: a case report. Issue 1 (December 2016) - Inoue, Akihiro; Ohnishi, Takanori; Kohno, Shohei; Mizuno, Yosuke; Kitazawa, Riko; Nakamura, Yawara; Ohue, Shiro
Abstract Background Multicentric gliomas are well-separated tumors in different locations of the brain, without anatomical continuity between lesions. We report a rare case of multicentric gliomas that occurred in both supra- and infratentorial regions with different histopathology. Case presentation A 27-year-old man was admitted to our hospital with mild motor weakness of the right leg. Magnetic resonance imaging (MRI) showed a large tumor occupying the left insula, extending to the left basal ganglia, so tumor resection was performed. Histological diagnosis was diffuse astrocytoma. Tumor cells showed sporadic immunoreactivity for p53 and negative immunostaining for epidermal growth factor receptor (EGFR). Postoperative course was uneventful, and adjuvant therapy was not performed. At 7 months after surgery, MRI disclosed a left cerebellar tumor displaying an irregular ring formation on enhancement with gadolinium (Gd) and marked peritumoral edema. MRI studies including T2-weighted imaging demonstrated that this paravermian tumor had no contact with the initial left insular tumor. In addition, MRI studies of the whole neuraxis, cytological examination of the cerebrospinal fluid, and neurological findings demonstrated that no dissemination had occurred through the subarachnoid space or as intracerebral metastases. Therefore, the second surgery was performed. Histological diagnosis was glioblastoma. Immunohistochemistry revealed that most tumor cells were positively stained for both p53 and EGFR but negatively stained for isocitrate dehydrogenase 1 (IDH1). Conclusions We reported a case of multicentric gliomas occurring in both supra- and infratentorial regions with different histopathology. Immunohistochemical examinations suggest that different genetic pathways may participate in the occurrence of these tumors.